Analisis Kebutuhan Pengembangan Multimedia Pembelajaran Berbasis Website pada Mata Kuliah Media Audio Radio - Ningsih, Sulia; Qosim, Arief; Sundari, Rini (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This research aims to present an analysis of the needs related to developing website-based multimedia learning tools for the Audio Radio Media course within the Educational Technology Study Program at Baturaja University. The study employed a quantitative descriptive approach, utilizing both observation and interview methods. The participants consisted of third-semester students from the program. Findings revealed that 85% of students experienced challenges in understanding practical content. Additionally, 85% of students reported insufficient time to fully grasp the material during on-campus sessions. Furthermore, 91% of students expressed strong enthusiasm for learning the course material, particularly through media that includes audio, video, and animation, which was favored by 88% of respondents. Supporting data also showed that 91% of students required media resources to study both theoretical and practical content, while 94% felt more motivated when learning with media. A significant 95% of students indicated a desire for more varied media use in learning. In addition, students are now more familiar and sensitive to the use of technology, so that the use of technology-based media such as computers and smartphones is considered appropriate with a percentage of 88%. Overall, the findings underscore the necessity of developing website-based multimedia learning for the Audio Radio Media course.